2004
DOI: 10.1002/ptr.1553
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant availability of turmeric in relation to its medicinal and culinary uses

Abstract: Turmeric (Curcuma longa) has been used in Indian cooking, and in herbal remedies. Its possible mechanism of action was examined in terms of antioxidant availability during actual cooking conditions and in therapeutic applications using standardized extracts. The assays involve different levels of antioxidant action such as oxygen radical absorbance capacity (ORAC), radical scavenging abilities using 1,1-diphenyl-2-picryl hydrazyl (DPPH), 2,2'-azobis-3-ethylbenzthiazoline-6-sulfonic acid (ABTS), ferric reducing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
3
7

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(89 citation statements)
references
References 21 publications
2
72
3
7
Order By: Relevance
“…Turmeric from Malaysia (Curcuma longa) has been reported to contain 0.094 mg/g of TFC of dry sample [24], while Sumazian et al [25] reported the presence of 4.05 mg/g of TFC of dry sample of Curcuma domestica. Similarly, Tilak et al [26] reported a TFC of turmeric from India ranging from 3.58 to 7.86 mg/g of turmeric. Polyphenols including flavonoids are extensively investigated in turmeric for their wide range of pharmacological activities [27].…”
Section: Flavonoid Contentmentioning
confidence: 89%
See 1 more Smart Citation
“…Turmeric from Malaysia (Curcuma longa) has been reported to contain 0.094 mg/g of TFC of dry sample [24], while Sumazian et al [25] reported the presence of 4.05 mg/g of TFC of dry sample of Curcuma domestica. Similarly, Tilak et al [26] reported a TFC of turmeric from India ranging from 3.58 to 7.86 mg/g of turmeric. Polyphenols including flavonoids are extensively investigated in turmeric for their wide range of pharmacological activities [27].…”
Section: Flavonoid Contentmentioning
confidence: 89%
“…These nonenzymatic antioxidants (phenolics and flavonoids) react with the prooxidants leading to inactivation. In the redox reaction, the antioxidants act as reductants and serve as the first-line defense to suppress the formation of free radicals [26]. According to previous reports, turmeric is a good source of natural flavonoids, which have been shown to have antioxidant activity, free radical-scavenging capacity, coronary heart disease preventive activities, and anticancer activities [28].…”
Section: Flavonoid Contentmentioning
confidence: 99%
“…In another set of experiments, the results obtained showed that the ORAC values of turmeric extract ranging from 10 to 25 µmoles of Trolox equivalent per gm fresh weight, are similar to or higher than the values observed for some fruits and vegetables including those for garlic (19.4), spinach (12.6) and onion (4.5) [69]. Ethanolic preparations of both raw and processed turmeric are effective in giving antioxidant protection at various levels [33].…”
Section: +mentioning
confidence: 62%
“…[14] Turmeric is also used in the treatment of dental diseases, digestive disorders such as dyspepsia and acidity, indigestion, flatulence, ulcers, antioxidant, antifertility as well to alleviate the hallucinatory effects of hashish, and other psychotropic drugs. [16][17][18] In food and manufacturing, curcumin is currently used in perfumes and as a natural yellow-coloring agent, as well as an approved food additive to flavor various types of curries and mustards. [19,20] Recent emphasis on the use of natural and complementary medicines in western medicine has drawn the notice of the scientific community to this ancient remedy.…”
Section: Medicinal Usesmentioning
confidence: 99%